Mind, brain, and schizophrenia - Williamson, Peter, 1953- (Oxford University Press, 2006)
1. The Evolving Concept of Schizophrenia. 2. Candidate Neuronal Circuits. 3. When Does Schizophrenia Begin?. 4. Clues from Drugs Which Affect Dopamine, Glutamate, and Other Neurotransmitters. 5. Clues from Psychophysiology. 6. Neuropsychological Studies. 7. Imaging Brain Structure in Living Patients. 8. Imaging Brain Function in Living Patients. 9. Imaging Brain Chemistry and the Question of Neuronal Degeneration. 10. Likely Components of the Final Common Pathway. 11. Early Models of the Final Common Pathway 1. Disconnection and Coordination. 12. Early Models of the Final Common Pathway 2. Bas.